Genome-Wide Association Analysis Reveals Different Genetic Control in Panicle Architecture Between Indica and Japonica Rice - Xufeng Bai (The Plant Genome, 2016)
Panicle architecture determines the number of spikelets per panicle (SPP) and is highly associated with grain yield in rice ( L.). Understanding the genetic basis of panicle architecture is important for improving the yield of rice grain. In this study, we dissected panicle architecture traits into eight components, which were phenotyped from a germplasm collection of 529 cultivars. Multiple regression analysis revealed that the number of secondary branch (NSB) was the major factor that contributed to SPP. Genome-wide association analysis was performed independently for the eight particle architecture traits observed in the and rice subpopulations compared with the whole rice population. In total, 30 loci were associated with these traits. Of these, 13 loci were closely linked to known panicle architecture genes, and 17 novel loci were repeatedly identified in different environments. An association signal cluster was identified for NSB and number of spikelets per secondary branch (NSSB) in the region of 31.6 to 31.7 Mb on chromosome 4. In addition to the common associations detected in both and subpopulations, many associated loci were unique to one subpopulation. For example, and were specifically associated with panicle length (PL) in and rice, respectively. Moreover, the -mediated flowering genes and were associated with the formation of panicle architecture in rice. These results suggest that different gene networks regulate panicle architecture in and rice.